Critical Thinking and Medieval Romance (Doctor Virtualis, 2025)
In Western Europe, practical reasoning, the deliberative process about things to be done constitutes a mode of critical thinking from the twelfth century on. Cathedral schools rely on the category of practical philosophy to address the exercise of prudentia. Academic instructions, known as accessus, rely on this category to address classical literature because it treats behavior. In the thirteenth century, scholastic developments resulting from the translation of Aristotle’s Nicomachean Ethics introduce syllogistic logic with the term ratio practica. The inner debates of courtly roance correlate with academic developments. Modeling critical thinking about ethical behavior, they represent the process of practical reasoning. Finding themselves in conflict, fictional speakers try to figure out the right thing to do. They consider circumstances and outcomes. However fictional, the representation of practical reasoning offers experiential complications and the difficulty of upholding prescriptive ethics.
Keywords: critical thinking; practical reasoning; prudence; courtly romance; inner debates